O‘QITUVCHI PSIXOLOGIYASI - Xolniyozov Xurshid Sobir o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The success of the education system depends, first of all, on the professional skills, personal qualities and psychological preparation of the teacher. The teacher is not only a provider of knowledge, but also a mentor who shapes the personality, influences the development of socio-moral views, and provides spiritual support to students. Therefore, modern pedagogy has turned the complex psychological study of the teacher’s personality into a separate scientific direction.